Improving and Maintaining Physical Activity and Anthropometric Indices in females from Tehran: Application of the Theory of Planned Behavior - Zeynab Gholamnia-shirvani; Fazllolah Ghofranipour *; Reza Gharakhanlo; Anoshirvan Kazemnezhad (Hamadan University of Medical Sciences, 2016)
Background and Objectives: The amount of physical activity as an essential determinant of healthy lifestyle in females is less than is required. Theory-driven health education interventions, particularly Theory of Planned Behavior (TPB), are effective in promoting and sustaining physical activity. This research evaluated the TPB-based educational intervention on exercise behavior and anthropometric indices in females residing in organizational houses in Tehran. Materials and Methods: A randomized controlled trial was performed on 130 females residing in institutional houses in Tehran (2014). Participants were randomly chosen with multi-stage cluster sampling. The instructional sessions were carried out applying modified methods of the TPB structure (instrumental and affective attitudes, subjective norms, perceived behavioral control, intention and behavior). The TPB constructs, physical activity level and intensity, Body Mass Index (BMI) and Waist Hip Ratio (WHR) were analyzed using the SPSS 16software in baseline, three and six months post-education. Results: Conducting the educational program led to a rise and maintained the mean of the TPB constructs and mean rank of the physical activity level and intensity, three and six months post-intervention in the case group (P<0.001). Also, the averages of Body Mass Index (BMI) and WHR decreased and sustained in temporal sections (P<0.001). However, no significant changes of aforesaid variables occurred in the control group (P>0.05) Conclusions: Implementing the TPB-directed instructional sessions resulted in ameliorating and sustaining exercise behavior and anthropometric indices in females.